PENINGKATAN KOMPETENSI KOMUNIKASI ORGANISASI SEBAGAI KUNCI WORK READINESS BAGI PESERTA DIDIK SMK AT-TAUFIQIYYAH - Wibowo, Cokorda Agung; Latif, Latif (Yayasan Education and Social Center, 2025)
The high open unemployment rate (TPT) among Vocational High School (SMK) graduates in Indonesia, reaching 9.01% as of August 2024, indicates a competency gap between graduates and industry needs. This gap is dominated by a deficit in soft skills, especially communication competence. This Community Service (PkM) program aims to enhance the work readiness of 12th-grade students at SMK AT-Taufiqiyyah by strengthening their organizational communication competencies. The program employed a blended-method approach, combining a presentation-lecture (cognitive knowledge transfer) and participatory, case-study-based Focus Group Discussions (FGDs) (practical skill application) for 50 students. Evaluation methods used quantitative pre-test/post-test to measure conceptual understanding, alongside qualitative observation during the FGDs. The results showed a highly significant increase in conceptual understanding, with the average pre-test score of 40.3 rising dramatically to 88.3 in the post-test (a 119.1% increase). Qualitatively, the FGD sessions demonstrated improved applied skills, active participation, collaboration, and the ability to apply theory. Student self-confidence in communication was also observed to increase. The blended-method approach (lecture + FGD) proved effective in bridging the theory-practice gap, enhancing holistic communication competence (cognitive, practical, affective), and supporting student work readiness.